Evaluation of nursing students' learning using realistic scenarios with and without debriefing - Rita de Cassia Silva Vieira Janicas; Nádia Zanon Narchi
Objective: to compare the clinical performance of nursing students in learning scenarios with and without debriefing in a simulation center. Method: a longitudinal, prospective, interventional, crossover randomized study, with a quantitative approach and before-and-after type, with a population composed of 120 nursing students distributed randomly between experimental and control group. The study phases included theoretical and demonstrative practice on child immunization; first Clinical Performance Test, which served as baseline measurement; randomization; scenarios with debriefing for the experimental group and without debriefing for the control group, according to clinical performance/intervention examination; exchange of groups or crossover; third Clinical Performance Test. Results: debriefing was proven to be effective in improving the performance of the students in the clinical exams, because improvement in the performance of the experimental group both in relation to the baseline measurement examination and in comparison with the control group in the post-intervention performance examination and in the third examination, after crossover (p<0.001). Conclusion: the use of scenarios with debriefing constitutes a strategy facilitating the teaching-learning process in the undergraduate nursing course.